1993
DOI: 10.1111/j.1365-2990.1993.tb00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal damage in fatal paediatric head injury

Abstract: The hippocampus is known to be frequently involved in head injury. In adults, such hippocampal lesions frequently include regions of selective neuronal necrosis. The present report examines the frequency and distribution of hippocampal damage in 37 cases of fatal head injury in children. Damage to the hippocampus was noted in 27 of 37 cases (73%). Lesions were often focal areas of selective neuronal necrosis located in the CA-1 subfield. Other subfields of the hippocampus were involved to lesser degrees. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 16 publications
1
15
1
3
Order By: Relevance
“…42,46,47,74 However, the literature is far from agreement on how the hippocampus is affected by trauma. In the current study, our finding of an unaltered number of migrating neuroblasts in the hippocampus of children following TBI is similar to the results of Chirumamilla and colleagues, 11 who did not observe increased neurogenesis in the hippocampus of adult rats 48 hours after fluid percussion injury.…”
Section: Discussionmentioning
confidence: 99%
“…42,46,47,74 However, the literature is far from agreement on how the hippocampus is affected by trauma. In the current study, our finding of an unaltered number of migrating neuroblasts in the hippocampus of children following TBI is similar to the results of Chirumamilla and colleagues, 11 who did not observe increased neurogenesis in the hippocampus of adult rats 48 hours after fluid percussion injury.…”
Section: Discussionmentioning
confidence: 99%
“…During experimental glaucoma, it has been observed that retinal ganglion cells in the glaucomatous eye die via apoptosis (Garcia-Valenzuela et al 1995). Moreover, autopsy of 37 cases of fatal head injury showed selective neuronal apoptosis in the hippocampal region of the brain (Kotapka et al 1993). An increase in nitrite in the cell culture medium was observed in response to shear in SH-SY5Y cells, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies in adults -autopsy, MRI volumetry and functional testing -indicate the presence of hippocampal injury in TBI. For example, in the majority of fatal cases, there is hippocampal damage of at least one CA1 subfield, and bilateral injury is present in approximately 75% [Kotapka et al, 1992[Kotapka et al, , 1993[Kotapka et al, , 1994. In fact, the degree of hippocampal atrophy is associated with the severity of TBI [Tate and Bigler, 2000], but not necessarily the presence of intracranial hypertension.…”
Section: Mri-derived Bioassay Of Pathophysiology In Tbimentioning
confidence: 99%